What's behind multiple institutional affiliations in academia? - Hanna Hottenrott; Cornelia Lawson (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Multiple institutional affiliations occur when an academic belongs to more than one organisation. Recent research shows an increase in multiple affiliations, but evidence on roles and motivations is mainly anecdotal. We develop in this study a typology of co-affiliations which identifies four types based on their purpose and origin. We draw on results from a unique international survey on academics in three major science nations (the UK, Germany and Japan) to study the different drivers for the four types of co-affiliations. The analyses show that researchers' motivations (access to networks, prestige, resources, funding, or personal income) explain the type of the observed co-affiliations. Self-initiated and research-focused co-affiliations are often motivated by networking and resource access while co-affiliations that serve other than research purposes are more often income motivated. The results contribute to the understanding of the organisation of science and we discuss implications for science and higher education policy.
Keywords: L3; O3; O5; 330; Institutional affiliations; academic labour market; resource access; k-meansclustering; Institutional affiliations; academic labour market; resource access; k-means clustering